STRUCTURE TRANSFORMATION AND SELF-ORGANIZATION PROCESSES IN DEFORMED CRYSTALS - Bohdan Koman; V. Yuzevych; R. Bihun (Електроніка та інформаційні технології, 2024)
The work investigates the patterns of self-organization processes in deformed semiconductor crystals of HgTe–CdTe solid solutions. It is claimed that crystal in the process of deformation should be considered as an open non-equilibrium thermodynamic system that evolves not only to preserve its integrity, but also to create new types of structures (defects) capable of more effectively dissipating the supplied energy. The formation of a synergistic structure in the crystal with minimal entropy is result. New types of dissipative structures were discovered. Mechanisms of effective dissipation of elastic energy are analyzed. The regularities of relaxation processes in deformed crystals at different stages of the deformation curve s–e. On the basis of electrophysical studies, the transformation of electroactive defects in the near-surface layers of micro- and macroplastically deformed HgTe–CdTe single crystals is analyzed. Self-organization in the "dislocation - point defect" system is realized by stable impurity atmospheres around freshly introduced dislocations. Shown process significantly depends on the type of impurity and the process temperature.